2014
DOI: 10.3139/147.110325
|View full text |Cite
|
Sign up to set email alerts
|

An Explanation of the Ageing Mechanism of Li-Ion Batteries by Metallographic and Material Analysis

Abstract: Li-ion batteries are a key technology for both electro-mobility and stationary energy storage systems. In order to be able to represent and improve their service life in these applications, a better understanding of the processes which lead to the degradation of the individual cells is essential. The work presented in this article focuses on the comparative post mortem analysis of type 18650 commercially available cells containing the state of the art active materials (Cathode: LiMn2O4 (LMO) and Li(Ni1/3Mn1/3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Such deformations were observed before in different types of commercial cells which usually also utilize welded tabs. [2,[14][15][16][17][18] The data of Bach et al suggested that pressure inhomogeneities in cylindrical cells lead to local Li deposition on the anode, which spreads out over the whole anode area when cells are further cycled, leading to a sudden capacity drop. [14] Figure 9 shows such a sudden drop of capacity after %700 cycles for the cells with welded tabs, however, not for the cells with foil tabs.…”
Section: Improvement Of Cycle Life By Foil Tab Designmentioning
confidence: 99%
“…Such deformations were observed before in different types of commercial cells which usually also utilize welded tabs. [2,[14][15][16][17][18] The data of Bach et al suggested that pressure inhomogeneities in cylindrical cells lead to local Li deposition on the anode, which spreads out over the whole anode area when cells are further cycled, leading to a sudden capacity drop. [14] Figure 9 shows such a sudden drop of capacity after %700 cycles for the cells with welded tabs, however, not for the cells with foil tabs.…”
Section: Improvement Of Cycle Life By Foil Tab Designmentioning
confidence: 99%
“…Tabs are likely to cause inhomogeneities in the jellyroll [2,3], since they are usually thicker than the electrode coatings (single-sided coating thickness for anodes < 100 µm [4]). Such inhomogeneities can lead to deformations of the jellyroll after long-term cycling, especially at increased C-rates [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Tabs are likely to cause inhomogeneities in the jellyroll [2,3], since they are usually thicker than the electrode coatings (single-sided coating thickness for anodes < 100 µm [4]). Such inhomogeneities can lead to deformations of the jellyroll after long-term cycling, especially at increased C-rates [2,3]. This should be different if the tabs were constructed from the current collecting foils themselves (Figure 1d), since they lead to less disturbed and therefore more homogeneous jellyrolls, which are closer to the mathematically ideal shape of an Archimedean spiral [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, for positive electrodes the main forms of aging are structural changes, such as phase transitions or structural disordering, chemical decomposition, or metal dissolution. Furthermore, the loss of electrical contact between (i) the active material particles and (ii) the active material particles and the conductive additive causes an increase in resistance in both electrodes and therefore aging is promoted. Among the positive electrode materials, LiMn 2 O 4 , LiNiO 2 , and LiCoO 2 transition-metal oxides have received increased attention; , however, to enhance specific capacity and thermal stability, research has been focused on LiNi x Mn y Co 1– x O 2 (NMC) layered oxides as positive electrode materials …”
Section: Introductionmentioning
confidence: 99%